Emotional dysregulation in children with attention-deficit/hyperactivity disorder - van Stralen, Judy (Attention deficit and hyperactivity disorders, 2016)
Emotional dysregulation is increasingly recognized as a core feature of attention-deficit/hyperactivity disorder (ADHD). The purpose of the present systematic literature review was to identify published data related to the neuropsychology of emotional dysregulation in children with ADHD. The literature obtained is discussed in the contexts of deficits in emotional control, impairments in executive function, the emotional components of comorbidities, neurophysiological and autonomic correlates of emotional dysregulation, and the significance of multiple neuropsychological pathways of ADHD on emotional dysregulation. These various lines of evidence are used to create a patient-oriented conceptual model framework of the pathway from stimulus to inappropriate internalized (sadness, moodiness) or externalized (anger, aggressiveness) emotional responses. The article concludes by calling for continued research into the development of reliable and universally accepted measures of emotional dysregulation in order to provide children affected with ADHD, and their caregivers, some explanation for their emotional lability and, ultimately, to be used as tools to evaluate potential treatments.